Grazing management in Inner Mongolia, China - Byrne, Anne Teresa, author; Hadrich, Joleen, advisor; Suter, Jordan, committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2016)
This thesis takes the form of two essays, both addressing issues of grazing management in Inner Mongolia, China. Inner Mongolia is home to numerous sheep and goat producers. Sheep and goat production has increased substantially in the past two decades as demand for meat in China has risen. This increase in production has placed pressure on the grasslands, leading to degradation and increased incidences of Mongolian locust outbreaks. The first essay addresses the question of economic vulnerability to grass loss. We use an equilibrium displacement model to model the livestock market in Inner Mongolia and simulate a market shock imposed by pasture grass loss. We find that herders are vulnerable to even small amounts of grass loss (~10%). The second essay addresses long term management strategies over the typical herder’s 30-year leasehold. We find that herders are better off changing their herd size from year to year in response to grass availability and that by using this strategy they can double their long-term profits.